Production efficiency as a mediating mechanism linking financial management and agricultural institutions to farm profitability - Musdalipa Musdalipa; Norhaedah; Sulfiana; Nurul Awaniah; Widyastuti Setianingsi Siri (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
This study examines how financial management and agricultural institutions are associated with farm profitability through production efficiency as a mediating mechanism. The unit of analysis is the individual farm business managed by food-crop farmers in Maros Regency, South Sulawesi, Indonesia. A quantitative explanatory design was used, and survey data from 150 farmers were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that financial management and agricultural institutions have positive and significant relationships with production efficiency, with path coefficients of 0.667 and 0.490, respectively. Production efficiency is also positively related to farm profitability (0.618), while the direct relationships of financial management (0.222) and agricultural institutions (0.203) with profitability remain significant but smaller than their mediated pathways. Bootstrapping results indicate significant indirect effects from financial management to profitability through production efficiency (0.412) and from agricultural institutions to profitability through production efficiency (0.303), confirming partial mediation. The model explains 64.3% of the variance in production efficiency and 75.3% of the variance in farm profitability. These findings suggest that managerial and institutional interventions are more likely to improve profitability when they are explicitly directed toward more efficient input use, cost control, and productivity improvement.